Penularan Papaya ringspot virus melalui Serangga Vektor dan Biji - Hidayat, Sri Hendrastuti; Harmiyati, Tutik; Adnan, Abdul Muin (Jurnal Fitopatologi Indonesia, 2022)
Insect Vector and Seedborne Transmission of Papaya ringspot virus Ringspot disease of papaya caused by Papaya ringspot virus (PRSV) is widely spread in Indonesia. Dissemination of this disease is known to occur through infected seedlings and aphid vectors. This study was conducted to determine transmission efficiency of PRSV through two aphid species, i.e. Aphis gossypii and Myzus persicae and to confirm that PRSV cannot be transmitted through seeds. Aphid transmission of PRSV isolate from Medan was carried out in papaya var. California with an acquisition feeding period and an inoculation feeding period of 10 minutes each. A minimum of 5 A. gossypii and 10 M. persicae were required for successful PRSV transmission. Transmission of PRSV by A. gossypii resulted higher disease incidence and more severe disease symptoms than transmission by M. persicae. Disease symptoms was not observed in all papaya seedlings grown from seeds extracted from fruits showing ringspot symptoms. Detection of PRSV by reverse transcription polymerase chain reaction method showed no amplification of specific DNA fragment of PRSV. The results of this study confirmed the potential of aphids as PRSV vectors and proved that PRSV was not seed borne.